The influence of practicum supervisors’ facilitation styles on student teachers’ reflective thinking during collective reflection - Foong, Lydia Yoke Yean; Md Nor, Mariani; Nolan, Andrea (Taylor & Francis, 2018)
Student teachers’ reflective thinking is closely associated with learning and improving practice. Novice student teachers require adequate support to reflect more deeply. The role of ‘others’ in collective reflection and knowledge generation as an outcome creates a platform for deep reflection, addressing both the processes and premises of reflective thinking. Facilitation styles of practicum supervisors could influence the level of student teachers’ reflective thinking during collective reflection. This is a case study using purposeful sampling involving a Malaysian teacher training institution that conducted an undergraduate early childhood programme in collaboration with a UK university. Sources of evidence were interviews, direct observations and documents. Data collected were analysed using both inductive and deductive methods. It was found that facilitation styles influence the depth of student teachers’ reflective thinking during group dialogic reflection. A continuum of facilitation styles from collaborative to instructive typologies was constructed. The implications of these findings are discussed.